2022
DOI: 10.3390/ijms231911257
|View full text |Cite
|
Sign up to set email alerts
|

Polo-Like Kinase 2 Plays an Essential Role in Cytoprotection against MG132-Induced Proteasome Inhibition via Phosphorylation of Serine 19 in HSPB5

Abstract: Protein homeostasis, including protein folding, refolding, and degradation, is thought to decline with aging. HSPB5 (also known as αB-crystallin) prevents target protein aggregation as a molecular chaperone and exhibits a cytoprotective function against various cell stresses. To elucidate the effect of HSPB5 on endoplasmic reticulum (ER) stress, we searched for novel binding proteins of HSPB5 using the proximity-dependent biotin labeling method. Proteins presumed to interact with HSPB5 in cells treated with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
0
0
Order By: Relevance
“…Some studies have shown that phosphorylated HSPB1 antagonizes apoptosis that is induced by TNF-α and TNF-related apoptosisinducing ligands by promoting the activation of pro-survival signaling pathways, including the TAK1-p38/ERK and SRC-AKT/ERK axes [183,184]. Other experiments have also demonstrated the importance of sHSPs' phosphorylation for their antiapoptotic function [41,85,185,186]. Blockade of HSPB6 phosphorylation at Ser16 was proven to suppress autophagy, thus exacerbating cardiac ischemia/reperfusion injury [187].…”
Section: Phosphorylation Regulates the Biological Functions Of Shspsmentioning
confidence: 99%
“…Some studies have shown that phosphorylated HSPB1 antagonizes apoptosis that is induced by TNF-α and TNF-related apoptosisinducing ligands by promoting the activation of pro-survival signaling pathways, including the TAK1-p38/ERK and SRC-AKT/ERK axes [183,184]. Other experiments have also demonstrated the importance of sHSPs' phosphorylation for their antiapoptotic function [41,85,185,186]. Blockade of HSPB6 phosphorylation at Ser16 was proven to suppress autophagy, thus exacerbating cardiac ischemia/reperfusion injury [187].…”
Section: Phosphorylation Regulates the Biological Functions Of Shspsmentioning
confidence: 99%